APLIKASI AUGMENTED REALITY DAN LOCATION BASED SERVICE KOLAM RENANG UMUM JAKARTA SELATAN BERBASIS ANDROID - Eris Dwi Purnama; Fahri Alfaruqi (LPPM Universitas Bina Bangsa, 2022)
Technological development of increasingly sophisticated mobile devices adds to the attractiveness of the user in use. as well as in terms of communicating may also serve in the search for information by acting as a map. GIS using GPS and maps to see in real time objects that exist in a region precisely in the unity of space and also the distance is based Location Based Service. Augmented reality is giving a new color to convey information created as a marker of the location of an object. For the layman connoisseurs and lovers of sports, especially swimming still not got the location of the object reference of the swimming pool. The information obtained was limited to an information from others and a text-only information.By looking at the above problems for some people who frequent sporting activities such as swimming certainly should know the places of public pools that will be used as a training tool. Reference locations and the location of the pool is visually obvious of course, can add instructions for people who want to go places. Augmented Reality and LBS is the right combination of information retrieval solutions to a location that makes the information visualized. The author makes Augmented Reality and LBS location Swimming Pool South Jakarta that aims to introduce a new way to convey information to people who do sports activities, especially swimming and also in order to facilitate outdoor sports lovers in the visited objects pool in this coverage is in the region South Jakarta